Beyond the qualitative description of complex magnetic nanoparticle arrays using FORC measurement. (9th April 2020) - Zamani Kouhpanji, Mohammad Reza; Stadler, Bethanie J H
Abstract: First-order reversal curve (FORC) measurements are broadly used for the characterization of complex magnetic nanostructures, but they can be inconclusive when quantifying the amount of different magnetic phases present in a sample. In this paper, we first establish a framework for extracting quantitative parameters from FORC measurements conducted on samples composed of a single type of magnetic nanostructure to interpret their magnetic properties. We then generalize our framework for the quantitative characterization of samples that are composed of 2–4 types of FeCo magnetic nanowires to determine the most reliable and reproducible parameters for a detailed analysis of samples. Finally, we conclude that the parameter with the best quantification potential, backfield remanence coercivity, does not require the full FORC measurement. Our approach provides an insightful path for fast, quantitative analysis of complex magnetic nanostructures, especially determination of the ratios of magnetic subcomponents present in multi-phase samples.